Hearing loss in the developing world : evaluating the i-Phone mobile device as a screening tool - Peer, Shazia (Division of Otorhinolaryngology, 2015)
Background: Hearing loss is a global health burden affecting 360 million people. The highest prevalence is in the Developing World where hearing screening programmes are scarce, and failure to address growing high-risk populations will result in new deaf communities. In resource stretched communities such as these, new strategies to alleviate this burden are necessary. Advances in technology have led to innovative mobile digital devices like smartphones and tablets with the potential to test hearing through audiometric applications. Given the recent upsurge of mobile technology in Africa, it is befitting to determine whether the implementation of science can translate to health service delivery. Objectives: To validate the Apple iPhone mobile device using the uHearâ„¢ application "app" as a possible hearing screening tool in the Developing World.